Determining health problems of child workers with the omaha system: example from a suburb of istanbul - KOLAÇ, NURCAN (My University, 2022)
Objective: This study assessed health problems of migrant and non-migrant child workers in lowersecondary schools from suburb of Istanbul with the Omaha system. Method: This descriptive and observational study was conducted in Istanbul. It comprised child workers. Descriptive Characteristics Assessment Form and Nightingale Notes Software based on the terminology of the Omaha System were used for data collection. Results: The participants were 81 child workers aged 10–13 years, 86% were male, and 12% were migrants from Syria. Eighty-five percent worked to contribute their family income. The most common health problems were mental health, neglect, low income, oral health, nutrition, personal care, physical activity, sleep and rest patterns, and neighbourhood/workplace safety. There was an association between mental health problems and family health status;between individual health status and oral health as well as role change;between maternal education level and oral health as well as personal care and between nutrition and paternal education level (p<.05). Conclusion: The Omaha system was found suitable for determining health problems of migrant and non-migrant juvenile labor. However, it is necessary to prevent poverty, develop the understanding of the social state, and comply with legal norms. We recommend that researchers examine the health of child workers in long-term and mixed-method observational studies

Amaç: Bu çalışmada, İstanbul'un kenar mahallelerinde bulunan ortaokullarda öğrenim gören göçmen ve göçmen olmayan çocuk işçilerin sağlık sorunlarının Omaha sistemiyle değerlendirilmesi amaçlandı. Yöntem: Tanımlayıcı ve gözlemsel çalışma olarak planlanan bu çalışma kapsamına İstanbul'da yaşayan çocuk işçiler alındı. Verilerin toplanmasında Tanımlayıcı Özellikler Değerlendirme Formu ve Omaha Sistemi terminolojisine dayalı Nightingale Notes yazılımı kullanıldı. Bulgular: Katılımcılar; 10-13 yaş arası 81 çocuk işçiden oluşmaktaydı. Çocuk işçilerin %86'sı erkek ve %12'si Suriye'den göç etmişti. Çocukların %85’i ailelerinin gelirine katkıda bulunmak için çalıştığını ifade etti. Çocuklarda en sık görülen sağlık sorunları ruh sağlığı, ihmal, düşük gelir, ağız sağlığı, beslenme, kişisel bakım, fiziksel aktivite, uyku ve dinlenme düzeni ve mahalle/iş yeri güvenliği gibi sorunlardı. İstatsitiksel değerlendirmede, ruh sağlığı sorunları ile aile sağlığı arasında; bireysel sağlık durumu ile ağız sağlığı ve rol değişikliği arasında; anne eğitim düzeyi ile ağız sağlığı ve kişisel bakım arasında; ve beslenme ile baba eğitim düzeyi arasında ilişki bulundu. Sonuç: Göçmen ve göçmen olmayan çocuk işçilerin sağlık sorunlarının belirlenmesinde Omaha Sistemi’nin uygun olduğu bulundu. Ancak bu kesimin sağlık sorunlarının çözümü için yoksulluğun ve çocuk işçiliğinin önlenmesi ve hukuk normlarına uyulması önerilmektedir. Ayrıca geniş örneklem gruplarında, uzun süreli ve karma yöntemli gözlemsel çalışmalarla çocuk işçilerin sağlığının incelenmesi önerilebilir.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Omaha sistemi; çocuk işçiliği; ruh sağlığı; ihmal; düşük gelir; ağız sağlığı; ortaokul çocukları; The Omaha system; child labor; mental health; neglect; income; oral health; secondary school children